Knowledge, Attitude and Practice of Ear care among Pre clinical Medical students at Birat Medical College Teaching Hospital. - Koirala, Bipin; Manandhar, Sriti; Shah, Rajeev Kumar (Birat Journal of Health Sciences, 2020)
Introduction: Ear care is a part of social cleanliness. It may not demand much care but proper and adequate care is essential to protect the optimal functions. The knowledge and awareness of ear care practice however is still lacking. Non –hygienic individual behaviors and habits like penetrating foreign objects, exposure to loud noise may affect the human ear. Lack of proper ear care may lead to many diseases and its complications.. Objectives : To assess the knowledge attitude and practice of ear care of pre clinical medical students attending Birat Medical College. To correlate the knowledge, attitude and practice of ear care of pre clinical medical students. Methodology: A descriptive cross sectional study was done in 151 students of pre clinical sciences of Birat Medical College for a period of two months from 15th Sept 2020 to 15 November, 2020. After the ethical clearance a specifically designed semi structured questionnaire containing yes and no questions was prepared in goggle form and distributed among all the pre clinical medical students of Birat Medical College Teaching Hospital students and then their response was evaluated. Result: Students of pre clinical sciences had good knowledge, attitude and practice of ear care. Significant correlation was seen between knowledge and practice and also between knowledge and attitude. However there was no significant correlation between attitude and practice. Conclusion: Overall knowledge, attitude and practice of preclinical medical students of Birat Medical College was good. Surprisingly students showed poor knowledge, attitude and practice in few individual questionnaires which was hoped that the medical students know more than lay individual in the society